Application and Implementation of E-Procurement Technologies in Malaysian Manufacturing Firm - Chan, Shiau Wei; Tiwari, Suman Tiwari Suresh; Ahmad, M.F.; Zaman, Izzuddin (International Journal of Supply Chain Management, 2019)
In the present scenario of global business competition, web-based technology is of great importance. It has become an extremely important criterion where businesses are now adopting e-commerce such as electronic procurement for the operation management of their organization. Despite this, they are still experiencing slow adoption of e-procurement. The main objective of this study was to determine the extent of e-procurement implementation in Malaysia organization as well as identify the relationship between the e-procurement system and supply chain performance among organizations in Malaysia. The study anchored on relevant theories on e-procurement which was Technology Acceptance Model. This study used descriptive research design. The population of this study was the employees from the manufacturing firms in Malaysia. A questionnaire was used to collect data. Data collected was analyzed quantitatively through the Statistical Package for the Social Sciences (SPSS). The procurement processes include E-ordering, E-sourcing, E-tendering, E-reverse auctioning and E-informing. The findings indicated that the firms had implemented E-procurement to a moderate extent. The respondents indicated that E-tendering was highly implemented in the organization in order to improve the supply chain performance to a large percentage (M=3.92, SD=0.701). The results also identified that the e-procurement system was positively associated with the supply chain performance of the organization. This study provides insights into manufacturing firms regarding the importance of E-procurement technologies.